Medial migration of grommet: Iatrogenic foreign body. (Bangladesh Journal of Medical Science, 2018)
Myringotomy and grommet insertion is a common surgical procedure in paediatric. It is relatively simple and safe procedure but few complications has been documented. We presented here a case of migration of grommet ventilation tube into the medial ear which is a very rare complication.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.493-495